Moderating effects of socio-cultural values on pro-environmental behaviors - Koon, Olivia; Chan, Ricky YK; Sharma, Piyush (Emerald, 2020)
Purpose: This paper aims to explain the discrepancy between pro-environmental intentions and behaviors with moderating effects of two socio-cultural values (espoused individualism and faith in others) on the link between intentions and actual behaviors to save electricity.